Key Principles of Governing Business-Incubator in University - M. V. Nachevskiy (Вестник Российского экономического университета имени Г. В. Плеханова)
Efficiency of economy development directly depends on implementation of measures supporting business entities, including upgrading entrepreneurial infrastructure. This problem was repeatedly discussed at the highest level of state governance of the Russian Federation, in particular within the frames of the President of Russian address to the Federal Assembly in 2021. Business-incubators are a key element of such infrastructure. It should be pointed out that specialized literature has not thoroughly studied the issue of business-incubators functions in today’s economy.  In general these functions can be differentiated in accordance with the stage of macro-economic development and overall strategy of finance and economic policy observed within the frames of a concrete state, depending on geopolitical situation, trends in global economy changes, possible foreign economic preferences and risks. Effectiveness of today’s incubator development, viewed both in finance and social aspect directly depends on the quality of methodological tools of their functioning efficiency appraisal. The article gives a classification of business-incubators by a number of important economic and managerial criteria, which gives a chance to find their most preferable type depending on strategic goals and objectives of developing the incubator’s founder and general functioning requirements of the relative territorial (federal, regional or municipal) system of entrepreneurial work support.  The author underlines that today’s business-incubator should possess a multi-sectoral character, it should be set up for the conventionally unlimited period, provide system and various finance support to residents , be integrated into space of digital economy, realize its own education programs of different profile and have a preventive model of management. Business-incubator is considered in two aspects. In a wider sense it is a specialized social and economic institution oriented to provision of long-term rise in intensity and finance and economic efficiency of entrepreneurial activity at the expense of favorable conditions for locating potentially competitive businessstructures at the initial stage of their life cycles on special territories.  In the narrower sense business-incubator is an entity of territorial (federal, regional or municipal) system of supporting entrepreneurial initiatives, which could ensure their progressive development at the expense of providing production, technological, finance, information, consultative and other resources on preference or free of charge basis.